The Curriculum Evaluation of Islamic Education Study Program of Tarbiyah and Teaching Sciences Faculty of State Islamic University of Raden Fatah Palembang - SUKIRMAN SUKIRMAN (Ta'dib: Jurnal Pendidikan Islam, 2018)
The aim of the study is to provide the information related to the accuracy of the curriculum composing in Islamic Education Study Program of Tarbiyah and Teacher Training Faculty of Islamic State University of Raden Fatah. It is an evaluative research using Countenance Stake model. To collect the data, the researcher used documentation, interview and questionnaire. In addition, the data were analyzed both qualitative and quantitatively. Moreover, the result shown that, in general, the curriculum in Islamic Education Study Program of Tarbiyah and Teacher Training Faculty of Islamic State University of Raden Fatah did not fulfil the minimum standard used, there were still some things must have been revised. By looking from the component of the curriculum itself, it only had three out of eight minimum components. Furthermore, by considering its framework of alumni profile it still did not meet any requirements to solve any problems and face any challenges which develop in the society. Additionally, the creating and arranging process were not through the selection of material evaluation, and they were not based on the correlation matric of material analysis and learning outcome. There was no agreement among related department forum in selecting material evaluation, and they were not based on the analysis of relevance between material evaluation and learning outcome. Furthermore, there were no material evaluation component, mapping matric of relevance between subject and learning outcome, and structured used was not clear enough. Related to curriculum implementation, there were some lecturers did not make any lesson plan, or the formats of their lesson plans were still using SAP format. There were many lesson plans having uncomplete component, and there were a lot of lesson plans which used learning outcome that was not relevant to learning outcome in the curriculum document. Besides, there were still 35.6% of meetings which were not based on time allocation, and most of task given by the lecturers were only in the form of article (47%) or making summary (25.2%). There were 27.4% lecturers which never used media in class, and the method used was mostly a conventional method that was teacher-centered learning (TCL), such as lecturing method (27.59%) and discussion (31.03%).